Модель управления обучением в условиях кредитно-модульной системы обучения - Тонконогий, В. М.; Попенко, Т. В.; Носов, П. С. (НТУ "ХПІ", 2009)
Automation of the education process management under the condition of the credit-modulus system is considered as an actual task of the modern education. The article proposes a double contour model of management and a functional diagram of the automated management system of the education process.
Keywords: инновации; интерактивные обучающие программы; электронные учебники; индивидуальный план